The effect of allowing motorists to opt out of tort law in the United States - O’Connell, Jeffrey; Carroll, Stephen; Abrahamse, Alan; Horowitz, Michael; Karan, Alexander (Les Cahiers de droit, 1998)
As applied to U.S. traffic accidents, both tort law and no-fault law are often attacked. A proposed solution would allow motorists to choose an option bypassing the inadequacies of both tort law and current U.S. no-fault laws. Actuarial estimates indicate large savings available to motorists so choosing. But as time goes on, the savings are diminished as low required limits of coverage in the U.S. meet inflation, leading not only to admittedly lessened savings but also to the anomaly of more and more motorists in non no-fault states pursuing tort rights for only economic losses.